Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content: 1. The reality of teaching strategies used by Arabic language teachers in primary stage to develop their students’ self-learning skills Co-Prof. Nawaf Saleh Al-Sulami, Ms. Amal Nasser Al-Harbi 2. The effects of teaching a book unit that contains controversial scholars’ opinions on the critical thinking of high school students Mr. Majdi Ahmed Hammad Aljohani, Dr. Mohammed Saad Alqarni 3. Obstacles to using learning platforms during the COVID-19 pandemic from the point of view of primary school teachers in Riyadh Ms. Noura Ghazi Al-Shaibani, Prof. Ahmed Mohammed Al-Hussein 4. Teachers’ practice of mathematical representation, and its relationship to the preschooler’s utilization of it in expressing mathematical ideas Mrs. Reem Khlifa Al-Owaidh, Co-Prof. Sama Fouad Khomais 5. The degree of inclusion of higher-order thinking skills in the mathematics textbook for the first year of secondary school in Kingdom of Saudi Arabia Mrs. Amal Ali Muhammad Al-Shehri